El género de no ficción en América Latina: caracterización a partir de dos obras pioneras, Relato de un náufrago y Operación masacre - Pinedo García, Peggy Paola (2021)
This article presents a characterization of nonfiction narrative in Latin America. To do this, two pioneering novels of this genre are taken as reference works: The story of a shipwrecked sailor (1955) by Colombian author Gabriel García Márquez, and Operation massacre (1957) by Argentine writer Rodolfo Walsh. The analysis of these works focuses on their influence on literature and journalism as initiators of a tradition that today is continued by authors who transit between narrative journalism and literature in this part of the continent. The article highlights that the two novels, considered as pioneers of the non-fiction genre in Latin America, were ahead of the classic In cold blood (1966) by American author Truman Capote. Also, the article explores the limits of the genre, whose literariness has been questioned due to its non-fictional nature.